STABILITY INDICATING HPLC DETERMINATION OF CILOSTAZOL IN PHARMACEUTICAL DOSAGE FORMS. - JOSE KURIEN; P. JAYASEKHAR (International Journal of Pharma and Bio Sciences, 2014)
A simple, selective, precise and stability indicating high performance liquid chromatographic (HPLC) method of analysis of Cilostazol in pharmaceutical dosage form was developed and validated. The chromatographic conditions consisted of a reversed phase C18 column (250 × 4.6 mm, 5µm) using a mobile phase containing a mixture of acetonitrile and acetic acid (0.1% aqueous solution) in the ratio of 50:50. Flow rate was 1ml/min. Detection was carried out at 260nm.The retention time of Cilostazol was 8.2 min. Cilostazol was subjected to acid and alkali hydrolysis, oxidation, photochemical and thermal degradation. The linear regression analysis data for the calibration plot showed a good linear relationship in the concentration range of 10 – 200 µg/ml. The value of correlation coefficient, slope and intercept were 0.99961, 44.25 and 130.3 respectively. The limit of detection and limit of quantification were 3 µg/ml and 10 µg/ml respectively. The method was validated for precision, accuracy, ruggedness and robustness. The drug was stable under acidic, basic, ultraviolet and thermal degradation conditions, but undergoes oxidative degradation in the presence of peroxides. All the peaks of degraded products were resolved from the active pharmaceutical ingredient with significant different retention times. This method is proposed to differentiate the drug from its degradation products very precisely; hence it can be employed as a stability indicating one.